Estudo da densidade de estocagem do camarão branco do pacífico Litopenaeus vannamei, em cultivo heterotrófico e autotrófico - Castro, Leandro Fonseca (2010)
The heterotrophic system has been implicated as an alternative to conventional intensive culture of marine shrimp. Previous studies have indicated that the production of microbial flocs under heterotrophic conditions can provide sufficient nutrients to operate under high shrimp density, even when low protein diets are used under little or no water exchange. This study aimed at evaluating the effect of Litopeneus vannamei stocking density on growth performance when farmed under autotrophic and heterotrophic experimental rearing conditions. The study was carried out over four consecutive phases. In the first study phase, 12 circular tanks of 1,000 L (bottom area of 1.02 m2) were used with of 50, 100, 200, 300, 400 and 500 shrimp/m2. Shrimp were stocked with a body weight of 13.31 ± 3.04 g and harvested after 15 days of rearing. In subsequent phases, 30 tanks were used allowing five replicates for each treatment. For phases 2 and 3, shrimp were farmed at 100, 150 and 200 animals/m2 under both heterotrophic and autotrophic conditions. In phase 4, stocking densities were reduced to 50, 75 and 100 shrimp/m2. Animals were farmed for 48, 51 and 72 days in study phases 2, 3 and 4, respectively. In the first stage of the study, treatments under 50 shrimp/m², 100 shrimp/m² and 200 shrimp/m² achieved a mean survival of 98.0 ± <0.001%, 91.0 ± 4.24% and 90,5 ± 2.83%, respectively. These treatments showed no statistical differences, although they differed from remaining treatments stocking densities equal to or greater than 300 animals/m2. Survival under treatments above 300 shrimp/m² fell substantially, particularly when it exceeded 400 shrimp/m². Under high stocking density, shrimp growth was reduced, with a drop in direct proportion to an increase in density. Under this condition, it also led to an increase in shrimp mortality when more than 150 shrimp/m² was used. Under moderate shrimp stocking densities, higher growth rates, survival and yields were achieved under the heterotrophic condition. Overall, results have indicated that an heterotrophic culture condition under a stocking density of up to 150 shrimp/m2 provided a lower risk of system collapse and the best shrimp growth performance.